@Ludomagalu: uma análise sobre a construção do ethos em tecnodiscursos no Instagram - Daldegan, Milian Cercal (2023)
This study aims to discuss the use of textual and rhetorical strategies employed as representations of the ethos of the @ludomagalu avatar in selected texts from its Instagram profile. We take as a starting point the use of rhetorical-argumentative strategies for the construction of the avatar and the way it makes its positioning (use of values) in order to influence and/or generate agreement. The theoretical framework is thus anchored in the Theory of Argumentation in Discourse (TAD – AMOSSY, 2010; 2016; 2020), especially regarding the notions of ethos and agreement, and in the Analysis of Digital Discourse (ADD – PAVEAU, 2021). The corpus consists of online statements – which reveal a composite nature, considering the human and non-human pair as inseparable in the constitution of digital productions. Our analyses were guided by three key questions: i) what are the possible principles for constructing the ethos of this avatar and what is its relationship with proposing an agreement with the audience? ii) what types of argumentative schemes would this avatar use in establishing agreement with the audience? Iii) how can the characteristics of these technodiscourses reveal aspects of the avatar’s ethos representation? Results from the analyses allowed us to observe that the avatar presents itself as embodying an image that represents femininity – a young, independent, multifaceted woman interested in technology, experiencing different situations, and also willing to discuss relevant subjects. These expressed meanings demonstrate an alignment with the audience, the establishment of agreement, engagement, and acceptance. Regarding the analysis of comments, it was also possible to observe that some interlocutors’ ethos were characterized in a similar manner to what was proposed in the source text, but they were also reconstructed when related to the image of the company, which, by offering a business proposal that is not always achieved, could generate dissatisfaction.